Adapting to a new normal during COVID-19: Leveraging the smart building system with BIM integration for lifecycle sustainability - Yong, Lim Chuin (Malaysian Institute Of Planners, 2022)
The COVID-19 outbreak brought challenges to the education sector in Malaysia as schools were shut down and later on, operate under strict standard operating procedures (SOP) and guidelines. This situation caused inconvenience to school authorities as the education process was significantly affected. Smart building systems that integrate various technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), mechanisms and robotics and building management systems allow school authorities to operate the schools under the new norm. Therefore, this research was conducted to propose a safe operation of the physical teaching and learning process in schools by leveraging smart building systems. A qualitative method was adopted which involved the participation of five schools in Kedah. Findings revealed that smart building systems are suitable to be implemented in schools to create a safe environment and operation for the physical teaching and learning process under the new norm. © 2022 by MIP.